The evolution of the stellar hosts of radio galaxies - Lacy, M; Bunker, A; Ridgway, SE (2000)
We present new near-infrared images of z > 0.8 radio galaxies from the flux-limited 7C-III sample of radio sources for which we have recently obtained almost complete spectroscopic redshifts. The 7C objects have radio luminosities ≈20 times fainter than 3C radio galaxies at a given redshift. The absolute magnitudes of the underlying host galaxies and their scale sizes are only weakly dependent on radio luminosity. Radio galaxy hosts at z ∼ 2 are significantly brighter than the hosts of radio-quiet quasars at similar redshifts and the recent model AGN hosts of Kauffmann and Haehnelt. There is no evidence for strong evolution in scale size, which shows a large scatter at all redshifts. The hosts brighten significantly with redshift, consistent with the passive evolution of a stellar population that formed at z ≳ 3. This scenario is consistent with studies of host galaxy morphology and submillimeter continuum emission, both of which show strong evolution at z ≳ 2.5. The lack of a strong "redshift cutoff" in the radio luminosity function to z > 4 suggests that the formation epoch of the radio galaxy host population lasts ≳ 1 Gyr, from z ≳ 5 to z ∼ 3. We suggest these facts are best explained by models in which the most massive galaxies and their associated AGN form early because of high baryon densities in the centers of their dark matter haloes.